Study on the influence of processing technology on the properties of 2024-T3 aluminum alloy - He, Jin; Feng, Hongfeng; Wen, Pengjun (International Journal of Electric Power and Energy Studies, 2023)
2024-T3 aluminum alloy is widely recognized for its low density and excellent mechanical properties. However, it has some shortcomings at high temperatures. Using Abaqus simulation technology, the surface heat source during the VIES (Variable Input Energy Source) treatment process was simulated, with the energy originating from the discharge channel. Through orthogonal experimental methods, it was indicated that the distribution and depth of the molten pool varied under different process parameters. Meanwhile, electric spark surface strengthening mainly affected the surface of the workpiece, with minimal impact on the internal structure. When the impact frequency is constant, increasing the input current enlarges the maximum heat flux density (Qmax) at the center, leading to an expansion of the molten pool area. Conversely, when the input current is constant, increasing the impact frequency shortens the contact time between the electric spark and the plate, resulting in reduced heat input from the electric spark. Consequently, the surface molten pool area decreases.